2020
DOI: 10.1371/journal.pone.0238984
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide genetic diversity and population structure of Garcinia kola (Heckel) in Benin using DArT-Seq technology

Abstract: Garcinia kola (Heckel) is a versatile tree indigenous to West and Central Africa. All parts of the tree have value in traditional medicine. Natural populations of the species have declined over the years due to overexploitation. Assessment of genetic diversity and population structure of G. kola is important for its management and conservation. The present study investigates the genetic diversity and population structure of G. kola populations in Benin using ultra-high-throughput diversity array technology (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…South region populations showed higher genetic diversity than those from the Central part. Populations of G. kola from Benin also revealed low levels of genetic diversity [ 25 ], which the latter authors attribute to the effect of domestication. However, the present study sampled wild individuals and did not discover any negative effect of domestication on genetic diversity ( Table 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…South region populations showed higher genetic diversity than those from the Central part. Populations of G. kola from Benin also revealed low levels of genetic diversity [ 25 ], which the latter authors attribute to the effect of domestication. However, the present study sampled wild individuals and did not discover any negative effect of domestication on genetic diversity ( Table 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing information gaps are limiting the potential improvement of the tree [ 23 ]. Only a few studies have focused on the morphological [ 6 , 23 , 24 ] and genetic diversity of G. kola [ 16 , 25 ]; however, none of them combined both approaches. Morphological diversity deals with the variation in quantifiable phenotypic traits such as fruit and seed weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different trends were also observed among natural stands of species other than palms. For example, Dadjo et al (2020) found only 0.86% genetic differentiation among sites in Garcinia kola (Heckel), which is an extensively utilized tree, and Wojnicka-Półtorak et al (2017) reported 13% genetic differentiation among age classes in natural populations of P. sylvestris.…”
Section: Discussionmentioning
confidence: 99%
“…Garcinia kola Heckel (Clusiaceae/Guttiferae) is an African rain forest plant whose seeds, best known as “Onie” in Fang-Beti languages (Cameroon, Gabon, and Equatorial Guinea), “Orogbo” in Yoruba language (Nigeria), or bitter kola, all over West Africa, are eaten recreationally and used in traditional medicine to treat T1D and malaria [ 18 20 ]. Early reports suggested that G. kola seeds have anti-inflammatory, antidiabetic, and neuroprotective properties [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%